2013
DOI: 10.1590/s0102-86502013000700003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pneumoperitoneum with carbon dioxide and helium on renal function and morphology in rats

Abstract: PURPOSE:To evaluate the effects of pneumoperitoneum with carbon dioxide and helium on renal function and morphology in a rat model. METHODS:Twenty four rats were randomized into three groups (n=8): gasless insufflation ('open', Pressure=0 mmHg), carbon dioxide pneumoperitoneum at 12 mmHg, and helium pneumoperitoneum at 12 mmHg; all lasting 90 minutes.. A cystostomy was performed and the bladder was emptied. At the end of the experiment, the urine produced, a blood sample and the left kidney of each animal were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The reduction of RPF was much more noticeable when IAP raised to 14 mmHg, but it became independent from the length of the insufflation interval [ 21 ]. These effects were less marked when, instead of CO 2 , helium or argon was insufflated intra-peritoneally [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Arterial Blood Supply and Renal Blood Flowmentioning
confidence: 99%
“…The reduction of RPF was much more noticeable when IAP raised to 14 mmHg, but it became independent from the length of the insufflation interval [ 21 ]. These effects were less marked when, instead of CO 2 , helium or argon was insufflated intra-peritoneally [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Arterial Blood Supply and Renal Blood Flowmentioning
confidence: 99%
“…21 These effects were less marked when, instead of CO2, helium or argon was insufflated intraperitoneally. [50][51][52][53][54] Further insights can be obtained from porcine models by examining the differences in flow dynamics between the medulla and the cortex upon increased intra-abdominal pressure. In a porcine model, the initial renal cortical blood flow was 5.5 times greater (50 ±18 vs 9 ±3 mL×min -1 ×100 g -1 [tissue]) than the medullary blood flow once the abdomen was insufflated and a laser-Doppler flowmetry probe was introduced into the renal parenchyma.…”
Section: The Effects Of Pneumoperitoneum On Renal Blood Flowmentioning
confidence: 99%
“…In another study, moderate hydropic degeneration and congestion were observed in both kidneys between the control group and the group where pneumoperitoneum was performed in the histopathological examination, but no significant difference detected. 27 In another study, however, in the histopathological examination of kidneys received from the rats, pathologic data varying from minimal alterations to moderate Acute tubular necrosis (ATN) in kidneys were obtained proportionally to increasing pressures. 7 When these results were considered, it could be thought that histopathological alterations occurring in kidneys change depending upon the duration to form pneumoperitoneum and the pressure of pneumoperitoneum formed.…”
mentioning
confidence: 99%